Geographic variation of life‐history traits in the sand lizard, Lacerta agilis: testing Darwin's fecundity‐advantage hypothesis. (12th February 2015) - Roitberg, E. S.; Eplanova, G. V.; Kotenko, T. I.; Amat, F.; Carretero, M. A.; Kuranova, V. N.; Bulakhova, N. A.; Zinenko, O. I.; Yakovlev, V. A.
Abstract The fecundity‐advantage hypothesis (FAH) explains larger female size relative to male size as a correlated response to fecundity selection. We explored FAH by investigating geographic variation in female reproductive output and its relation to sexual size dimorphism (SSD) in Lacerta agilis, an oviparous lizard occupying a major part of temperate Eurasia. We analysed how sex‐specific body size and SSD are associated with two putative indicators of fecundity selection intensity (clutch size and the slope of the clutch size–female size relationship) and with two climatic variables throughout the species range and across two widespread evolutionary lineages. Variation within the lineages provides no support for FAH. In contrast, the divergence between the lineages is in line with FAH: the lineage with consistently female‐biased SSD (L. a. agilis) exhibits higher clutch size and steeper fecundity slope than the lineage with an inconsistent and variable SSD (L. a. exigua). L. a. agilis shows lower offspring size (egg mass, hatchling mass) and higher clutch mass relative to female mass than L. a. exigua, that is both possible ways to enhance offspring number are exerted. As the SSD difference is due to male size (smaller males in L. a. agilis), fecundity selection favouring larger females, together with viability selection for smaller size in both sexes, would explain the female‐biased SSD and reproductive characteristics of L. a. agilis. The pattern of intraspecific life‐history divergence in L. agilis is strikingly similar to that between oviparous and viviparous populations of a related species Zootoca vivipara. Evolutionary implications of this parallelism are discussed.